State in Perplexity:The Politics of Water Rights and Irrigation System Turnover in Tamil Nadu - Rajagopal, A.; Janakarajan, S. (Water Nepal, 2009)
The authors trace out the history of water rights and water laws in Tamil Nadu and their relevance to water resource management in today's India. They discuss traditional water rights that have been practicing by users communities for centuries, and analyse their strength and weakness as well as how state of Tamil Nadu appropriated the rights. The paper explores problems associated with the state's management of water, the recent attempts to transfer water management functions to users committees. Keywords: politics; water rights; irrigation systems Water Nepal Vol. 12, No. 1&2, 2006 Page: 115-142